Geek Girl Rising : Inside The Sisterhood Shaking Up Tech - Heather Cabot, Samantha Walravens (St. Mertin's Griffin, 2017)
Meet the women who haven't asked for permission from Silicon Valley to chase their dreams. They are going for it -- building the next generation of tech start-ups, investing in each other's ventures, crushing male hacker stereotypes and rallying women and girls everywhere to join the digital revolution. Geek Girl Rising isn't about the famous tech trailblazers you already know, like Sheryl Sandberg and Marissa Mayer. Instead, veteran journalists Heather Cabot and Samantha Walravens introduce readers to the fearless female entrepreneurs and technologists fighting at the grassroots level for an ownership stake in the revolution that's changing the way we live, work and connect to each other.